Peningkatan Kemampuan Mengenal Huruf Hijaiyah Melalui Media Flashcard Pada Anak Kelompok A di RA Miftahul Huda Nogosari - Alda Salma Rizqy Ilahi; Nahdiyatul Ummah (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
Flashcards are a visual medium used to display information such as names or pictures on one or two objects used in a lesson or learning activity. It is often used by parents and teachers to teach children about understanding and learning from information about a subject. This research will examine: 1) How the hijaiyah letter flashcard media is applied to group A children at RA Miftahul Huda Nogosari, 2) whether the hijaiyah letter flashcard media is effective in improving students' ability to recognize hijaiyah letters. Meanwhile, the aim is to determine the application of hijaiyah letter flashcard media carried out by educators for group A children at RA Miftahul Huda Nogosari and also to determine the effectiveness of hijaiyah letter flashcard media in improving students' ability to recognize hijaiyah letters. The type of research used is quantitative, as well as experimental using pretest and posttest without comparison classes. Then, to find out the level of effectiveness, use the Paired Sample Test. Research conducted at RA Miftahul Huda Nogosari found that children's ability to learn hijaiyah letters without flashcard media was limited so that many were not able to memorize hijaiyah letters. Research has found that the use of flashcards is effective in improving children's ability to learn hijaiyah letters, because they provide a good learning experience and help students understand the meaning of hijaiyah letters. Apart from that, using flashcards can increase children's interest and understanding of hijaiyah letters, because each flashcard has a different color. Keywords: Flashcard, hijaiyah letters